2019
DOI: 10.1111/1462-2920.14852
|View full text |Cite
|
Sign up to set email alerts
|

Diet shapes cold‐water corals bacterial communities

Abstract: For the cold-water corals (CWC), living in the deep and dark ocean, heterotrophs are the key microbiome partners of the host. The role of the CWC microbiome and the type of association to the host remain however poorly known. In this paper we tested whether diet shapes the composition of the bacterial community associated to the two most common cold water coral species: L. pertusa and M. oculata. We demonstrate that a large portion of the corals" bacterial community represents a food influenced microbiome. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…Seasonal changes in the relative abundances of Tenericutes and Proteobacteria that we found in P. crucis and E. tourneforti collected from the back reef are similar to seasonal changes reported in the microbiomes of temperate gorgonian corals (van de Water et al, 2018b). This seasonality may reflect changes in gorgonian diets (Cocito et al, 2013), similar to changes in diet influencing the microbial communities of deep sea scleractinian corals (Galand et al, 2020). While the relative abundances of Tenericutes and Proteobacteria changed seasonally, the dominant bacteria generally remained stable.…”
Section: Discussionsupporting
confidence: 82%
“…Seasonal changes in the relative abundances of Tenericutes and Proteobacteria that we found in P. crucis and E. tourneforti collected from the back reef are similar to seasonal changes reported in the microbiomes of temperate gorgonian corals (van de Water et al, 2018b). This seasonality may reflect changes in gorgonian diets (Cocito et al, 2013), similar to changes in diet influencing the microbial communities of deep sea scleractinian corals (Galand et al, 2020). While the relative abundances of Tenericutes and Proteobacteria changed seasonally, the dominant bacteria generally remained stable.…”
Section: Discussionsupporting
confidence: 82%
“…The different habitat preferences may be associated to the different physiological characteristics of the two species coupled to the different hydrological features defining the two sites in the canyon. Lophelia pertusa and M. oculata exhibit distinct physiological functions, including skeletal growth rates (Lartaud et al, 2014), feeding behavior and preferences (Tsounis et al, 2010;Galand et al, 2020), reproduction cycles (Waller and Tyler, 2005), but also distinct associated microbial communities (Meistertzheim et al, 2016). Different patterns of distribution between L. pertusa and M. oculata have been reported in the Atlantic and Mediterranean regions where M. oculata is the dominant species in the mid slope while L. pertusa is more abundant in the down slope (Foubert et al, 2011;Fabri et al, 2017;Boolukos et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Both Lophelia pertusa and Madrepora oculata feed mostly on zooplankton, but it has been demonstrated that they do not share the same metabolism (Gori et al, 2014). Analyses of lipid compositions, and their nitrogen isotopic signatures, suggest that the two species adopt different feeding strategies (Kiriakoulakis et al, 2005;Galand et al, 2020). Lophelia pertusa is a more opportunistic suspended feeder, so its capacity to catch enough prey to sustain growth may be higher compared to M. oculata (Mueller et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations